The Art of Scrum How Scrum Masters Bind Dev Teams and Unleash Agility - McKenna, Dave (Apress : Imprint: Apress, 2016)
This book covers the nuts and bolts of scrum-its framework, roles, team structures, ceremonies, and artifacts-from the scrum master's perspective. The Art of Scrum details the scum master's responsibilities and core functions in planning and facilitating the ceremonies and artifacts of a scrum team: sprint planning, sprint execution, backlog refinement, daily standups, sprint reviews, and sprint retrospectives. It analyzes the scrum master's interactions with other scrum roles, including the product owner, development team members, other scrum masters, and the agile coach. It details the soft skills a scrum master uses to coach a group of individuals and turn them into a high performing scrum team. This book is for scrum masters and all readers whose scrum and stakeholder roles bring them into contact with scrum masters. Scrum Master Dave McKenna catalogs the three skill sets that scrum masters must master to be successful at binding teams and unleashing agility: soft skills, technical skills, and contingency skills. The author illuminates his examination of these skill sets with insights and anecdotes drawn from his own experience as an engineer, agile coach, and scrum master. He illustrates common mistakes scrum masters make, as well as modeling successful strategies, adaptations to changes, and solutions to tricky problems. From reading The Art of Scrum, scrum masters, product owners, dev team members, and all interested scrum stakeholders-executive sponsors, project managers, functional and line managers, administrative personnel, expert consultants, testers, vendors, and end users-will learn how scrum masters go about building agile teams that consistently deliver value and continuous improvement by deploying the following actions, methods, and strategies: • Facilitating team members' self-organization and cross-functionality • Aligning scrum stakeholders to sprint goals and shield their teams from interference • Baking automated continuous integration and testing into backlog refinement • Meeting contingencies such as intra-team conflicts, organizational impediments, technical debt, disrupted cadence, personnel changes, scope creep, and sprint goal failure.